2010
DOI: 10.1111/j.1365-2133.2010.09827.x
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod simultaneously induces autophagy and apoptosis in human basal cell carcinoma cells

Abstract: This study not only demonstrates that imiquimod can directly induce autophagy and apoptosis in BCC cells, but also shows the cooperation and coordination between these two processes to induce cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 38 publications
(87 reference statements)
6
42
0
2
Order By: Relevance
“…Previous studies have shown that inhibition of autophagy can aggravate apoptosis [27,28] and that inhibition of apoptosis can induce autophagy in A549 cells [47], suggesting the two processes are linked physiologically. To determine whether effects of naphthazarin on apoptosis and autophagy are independent, or are a consequence of one process affecting the other, we analyzed cells treated with naphthazarin in the presence of either apoptosis or autophagy inhibitors (zVAD-fmk or 3MA, respectively).…”
Section: Autophagy and Apoptosis Occur Independently Upon Naphthazarimentioning
confidence: 98%
“…Previous studies have shown that inhibition of autophagy can aggravate apoptosis [27,28] and that inhibition of apoptosis can induce autophagy in A549 cells [47], suggesting the two processes are linked physiologically. To determine whether effects of naphthazarin on apoptosis and autophagy are independent, or are a consequence of one process affecting the other, we analyzed cells treated with naphthazarin in the presence of either apoptosis or autophagy inhibitors (zVAD-fmk or 3MA, respectively).…”
Section: Autophagy and Apoptosis Occur Independently Upon Naphthazarimentioning
confidence: 98%
“…IMQ simultaneously induces autophagy and apoptosis in skin BCC cells [12]. Under metabolic stress, AMPK promotes autophagy by directly activating ULK1 through Ser 317, Ser 555 and Ser 777 phosphorylation [19].…”
Section: Imq-induced Autophagy Is Independent Of Ampkmentioning
confidence: 99%
“…Two major anti-tumoral mechanisms of IMQ, i.e., direct cancer cell death through the induction of apoptosis and autophagic cell death, have been reported. IMQ induces membrane-death receptor-independent apoptosis in various skin cancer cells [9,10] as well as autophagic cell death in Caco-2 colon cancer cells and BCC cell lines [11,12]. IMQ rapidly depletes Mcl-1 protein levels via translation inhibition in skin cancer cells, and Mcl-1 over-expression results in resistance to IMQ-induced apoptosis [13].…”
mentioning
confidence: 99%
“…First, imiquimod may induce programmed death of gastric cancer cells, such as autophagy and apoptosis. Accumulating evidence indicates that TLR7 activity is not restricted to the elicitation of innate and adaptive immune responses, but directly triggers programmed cell death in various types of cancer, such as melanoma and colon cancer (16,27). Second, TLR7 is selectively expressed in plasmacytoid dendritic cells (pDCs).…”
Section: Discussionmentioning
confidence: 99%